Cohabitation in sub-Saharan Africa: Does women empowerment matter? Insights from the demographic and health survey - Castro Ayebeng; Joshua Okyere; Nancy Arthur; Kwamena Sekyi Dickson (PLoS ONE, 2025)
Background Cohabitation is increasingly challenging traditional family structures in sub-Saharan Africa (SSA), marking a significant cultural shift in the region. This rise in non-traditional unions prompts an exploration into the underlying factors, particularly the influence of women’s empowerment. Despite the growing prevalence of cohabitation, there remains a notable gap in research examining its connection to women empowerment. This study aims to bridge that gap by investigating the intricate relationship between key indicators of women’s empowerment and cohabitation in SSA, offering fresh insights into how changing gender dynamics may be reshaping intimate partnerships in the region. Methods The study is a secondary data analysis of the Demographic and Health Survey (DHS) data of 13 SSA countries. A sample of 124,183 women between the ages of 15 and 49 having information on the outcome of interest were included in the analysis. Descriptive and inferential analyses, including proportions, Pearson’s Chi-squared test, and multivariable logistic regression models, were employed to examine the association between women’s empowerment indicators and cohabitation. The final regression model is presented in adjusted odds ratios (aOR) with 95% confidence intervals (CI). Results We found that cohabitation among women varies widely in SSA, with an overall prevalence of 10.9%—ranging from 50.6% in Liberia to just 0.1% in Senegal. We observed that women with higher levels of acceptance of spousal violence, greater decision-making capacity, and increased general knowledge level were more likely to enter cohabiting relationships. In contrast, women aged 25 and above, those residing in rural areas, those from wealthier households, and those with religious affiliations were less likely to cohabit. Additionally, women whose partners had primary or secondary education had higher odds of cohabitation compared to their counterparts whose partners had no formal education. Conclusion We conclude that women’s empowerment plays a significant role in the rising cohabitation rates in SSA. We postulate that addressing adolescent pregnancies could have a significant impact on reducing the practice of cohabitation among women of reproductive age in SSA. Research directions require longitudinal studies to understand the evolving relationship between empowerment and relationship choices, as well as qualitative inquiries to reveal underlying motivations, and comparative analyses across diverse cultural contexts to deepen insights into the interplay between empowerment and cohabitation decisions.